Follicular dendritic cell sarcoma of the uterine cervix: a case report - Takuto Nakamura; Masato Yoshihara; Satoshi Tamauchi; Hiroaki Kajiyama; Fumitaka Kikkawa (BMC, 2020)
Abstract Background Follicular dendritic cell sarcoma (FDCS) is a rare mesenchymal tumor that mostly occurs in systemic lymph nodes. FDCS in the uterine cervix has not yet been reported. Case presentation A 49-year-old woman was referred to our department with a cervical tumor, which was histologically suspected to be undifferentiated carcinoma. She underwent hysterectomy, salpingo-oophorectomy, and pelvic lymphadenectomy after neoadjuvant chemotherapy with paclitaxel and carboplatin. The resected specimen contained high numbers of spindle cells and was immunohistochemically confirmed to be FDCS. The tumor was completely resected and recurrence was not detected at a 16-month follow-up. Conclusion FDCS is an extremely rare malignant tumor in the uterine cervix, and an accurate diagnosis and complete resection are essential for a good prognosis.